VALIDITAS HANDOUT FISIKA DASAR BERBASSIS KETERAMPILAN BERPIKIR KRITIS DALAM STRATEGI PEMBELAJARAN PROBLEM BASED LEARNING DI STKIP PGRI SUMATERA BARAT - Megasyani Anaperta; Helendra Helendra (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Learning strategies can be designed by the faculty in a method or learning strategies used by lecturers so that learning becomes meaningful. So that students do not feel burdened by the teaching material that must be mastered. If the students themselves are looking for, cultivate, and concludes on the issues learned, the knowledge that he will get longer embedded in the mind. This type of research is the development of research. This handout development model development model proposed by Plomp (2010) which consists of the initial investigation phase (preliminary research), design and realization phase (prototyping phase), and (3) phase assessment (assessment phase). In this study conducted a preliminary investigation phase dalah and perancangan.Teknik data collection to determine the validation Handout Based Critical Thinking Skills in Problem Based Learning Strategies Learning is observation and questionnaires. Validation device is performed to determine whether the devices are made valid to be tested or not. The results of the validation provided by validator learning dikembangkan.isi Hand Out that has been designed to have a very valid category. This is evident from the contents of the feasibility of the value of 93 is given validator. Construction Hand Out gain value 94 which means also categorized as very valid. The use of Indonesian obtain the value of 93. This means that Indonesian used in Hand Out also been very good. Keywords: Handout, Validity, basic physics, Problem Based Learning